A review on oil palm physiology under water stress / Muhammad Izzat Arif Zulkafli - Zulkafli, Muhammad Izzat Arif (Faculty of Plantation and Agrotechnology, 2017)
The African oil palm (Elaeis guineensis Jacq.) is of great social and economic importance for millions of people in the tropics and subtropics. Water supply is the main yield-limiting abiotic factor of oil palm. In this review paper, physiological data are presented in a perspective to provide a sight of the behavior of oil palm trees facing water deficit. The vapor pressure deficit (VPD), proline content and sex ratio were studied. The stomatal conductance (gs) was highly correlated with the VPD. Lower gs was observed when VPD reached values >1.5 kPa. A significant reduction has also been noted in the transpiration rate and photosynthetic rate in high VPD in the environment. The proline content increased to different degrees with the extension of water stress. Lower sex ratio was observed when subjected to water stress, where there was high number of male flower production detected. Thus, oil palm possibly showed different response mechanisms under water stress.